2012
DOI: 10.1111/j.1532-849x.2012.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fracture Resistance in Aqueous Environment of Four Restorative Systems for Posterior Applications. Part 1

Abstract: Fracture resistance of monolithic lithium disilicate in an aqueous environment is promising and requires second phase testing to evaluate the potential of various thicknesses appropriate for posterior single tooth applications. Doubling the IPS e.max Zirpress zirconia core from 0.4 mm to 0.8 mm increased the fracture resistance of this restorative system threefold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Their study did not fatigue specimens and used LAVA Plus (3M ESPE) zirconia and e.max Press (Ivoclar Vivadent) lithium disilicate bonded with a resin cement. Dhima et al 14 recorded lower values (743 N for 2-mm-thick lithium disilicate and 1106 N for 2-mm-thick bilayered zirconia). Their study was performed with e.max ZirPress (Ivoclar Vivadent) zirconia, and fracture testing was performed under water.…”
Section: Discussionmentioning
confidence: 96%
“…Their study did not fatigue specimens and used LAVA Plus (3M ESPE) zirconia and e.max Press (Ivoclar Vivadent) lithium disilicate bonded with a resin cement. Dhima et al 14 recorded lower values (743 N for 2-mm-thick lithium disilicate and 1106 N for 2-mm-thick bilayered zirconia). Their study was performed with e.max ZirPress (Ivoclar Vivadent) zirconia, and fracture testing was performed under water.…”
Section: Discussionmentioning
confidence: 96%
“…Previous in vitro investigations showed that monolithic zirconia SCs exhibited fracture loads higher than those of layered zirconia restorations (Dhima et al 2013;Sun et al 2014;Lan et al 2015). Recently, an in vitro analysis reported that monolithic zirconia crowns with an occlusal thickness of 0.5 mm showed sufficient fracture resistance to withstand occlusal loads in the molar regions (Nakamura et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2 However, clinical longevity cannot be accurately predicted based on these properties or from in vitro load-to-failure tests. [3][4][5][6] Most of these systems have been brought to market with almost no independent clinical testing. Ninety-five percent of metal ceramic restorations are intact and functioning at 11 years.…”
mentioning
confidence: 99%